Study of ecology of malnutrition with respect to infection, infestation pattern, immunization and feeding practices in children attending tertiary care hospital - Kabbin, Gautam M.; Chavan, Vinod P. (International Journal of Contemporary Pediatrics, 2016)
Background: It often quipped that half of the world is starving and other half is tyring to lose weight!!.Unfortunately India is in the former half of the world. Out of 667 million children under age five worldwide, 151 million children are stunted and 50 million children are wasted. Methods: The present study showed a very poor immunization status of malnourished children only 7.26% were completely immunized and 74.39% and 8.47% of malnourished children were partially immunized and unimmunized respectively. Study also showed a high incidence of wrong feeding practices like early weaning, prolonged exclusive breast feeding without adequate supplementation, and top feeding in the malnourished cohort. Study also showed a high prevalence of bronchopneumonia, UTI, GI infections in the study group. Tubercular meningitis, pyogenic meningitis, aspiration pneumonia contributed to majority of deaths. Malnourished children are more likely to have anemia, xerophthalmia, bacteremia, bacteriuria, pneumonia, GI infection and tuberculosis. The study was conducted in the Department of Pediatrics, VIMS and Head Quarters Hospital Bellary from December 2006 to December 2007. Results: In this study out of 8 HIV positive children 6 children had been breast fed and 2 were top fed. Study also showed a high prevalence of bronchopneumonia, UTI, GI infections in the study group. Tubercular meningitis, pyogenic meningitis, aspiration pneumonia contributed to majority of deaths. Malnourished children are more likely to have anemia, xerophthalmia, bacteremia, bacteriuria, pneumonia, GI infection and tuberculosis. In cases with severe malnutrition, screening for HIV infection must be done. Conclusions: Education regarding early initiation of breast feeding within one hour of birth, exclusive breast feeding for 4 to 6 months and continued breast feeding for 2 years or beyond with adequate supplementation must be emphasized. Last but not the least, the importance of immunization in breaking the vicious cycle of infection and malnutrition should be made known to the community at large through effective usage of mass media.